Redução da dose de radiação em pacientes e equipes médicas pelo uso de filtros adicionais de cobre e alumínio nas saídas de tubos de raios X em equipamentos de hemodinâmica - Weis, Guilherme Lopes (2011)
The use of ionizing radiations, x-rays, are the services of hemodynamic which aim to perform the diagnosis and the therapy of many kinds of heart illnesses. In the Services of Hemodynamic the most preoccupying aspects concerning the levels of radiation exposure not only of the patients but of medical team as well, is the time of which exposure occurs. As means of reducing the time of total exposure which is extremely dependent on the behavior of the professionals during the procedure, it can be cited the reduction of the time of the total exposure the position of the team into the room, the use of equipments of individual protection, and the distance of the tube intensifier of the images concerning the patient, among other factors. The application of these means of reduction of the exposure is variable according to the medical teams. So, the proposal of this work is to reduce the levels of exposure of an independent form of that form the medical team are using these equipments. It is proposed the use of additional filters in the exit of the x-ray in the three equipments of different generations, HEMOCOR SM - Interventionist Cardiology, Heart Institute - ICOR and the University Hospital of Santa Maria-HUSM, with the main objective of reducing the radiation of low energy that increase the exposure of patients and medical team. The principal difficulty faced with the use of the filters is the reduction of the quality of the image, that is, the loss of information aiming to correct the diagnosis. In order to quantify the quality of the image, a simulator was mounted with plates of aluminum and with other devices overlapping them to make it possible to measure and to compare the obtained images. In order to avoid doubting the evaluation of the images produced among the observers (inter-observers) and even among the own observatory (intra-observer), methods of analyze of images (threshold, histogram, surface 3D) was used, where it is possible to measure the relation sign noise, the special resolution, the contrast and the definition of the area of the sign. It was used ionization chambers which were placed in the position of the entrance of the skin of the patient, in the entrance in the tube intensifier and in the position of the hemodynamic doctor in order to quantify the reduction of doses when the filters were added. After they chose of the ideal filter for every type of the equipment, it was measured the effective dose of hemodynamic , using personal dosimeters during the clinical procedures. These effective doses were compared with those obtained without the use of filters for the same clinical procedures. So, it was possible to quantify the real reduction of the exposure of the medical team. In the case of HUSM, in the fluoroscopy-type, the adding filtration of 0,29 mm of Cu more 1 mm of Al showed the better results, allowing a reduction in the Rate of Kerma in the Air in the Entrance of the Skin of the Patient of 55,89% and a reduction of Rate of Kerma in the Air at 70 cm of distance in the direction of the hemodynamic doctor of 38,8%. Already, in the pencil-type, the additional filtration of 0,29 mm of Cu plus 2 mm of Al showed better results, allowing a reduction in the Rate of Kerma in the Air in the Entrance of the Skin of the Patient at 80,3% and a reduction of Rate of Kerma in the Air at 70 cm of distance in the direction of the hemodynamic doctor of 68,55%. For the HEMOCOR, in the fluoroscopy-type the additional filtration of 0,29 mm de Cu plus 2 mm of Al presented better results, allowing a reduction in the Rate of Kerma in the Air in the Entrance of the Skin of the Patient of 48,81% and a reduction in the Rate of Kerma in the Air at 70 cm of distance in the direction of the hemodynamic doctor of 23,91%. Already in the pencil-type, the additional filtration of 0,29 mm de Cu more 2 mm of Al presented the better results, allowing a reduction in the Rate of Kerm in the Air in the Entrance of the Skin of the Patient of 72,53% and a reduction in the Rate of Kerma in the Air at 70 cm of distance in the direction of the hemodynamic doctor of 52,30%. For the ICOR, in the fluoroscopy-type, it was not possible to collect information, because the equipment does not produce images DICOM, nor it keeps the last image in the monitor. Already, in the pencil-type, the additional filtration of 0,58 mm of Cu plus 1 mm of Al presented better results, allowing a reduction in the Rate of Kerma in the Air in the Entrance of the Skin of the Patient of 82,27% and a reduction in the Rate of the Kerma in the air at 70 cm of distance in the direction of the hemodynamic doctor of 75%. In the analysis of the personal dosimeter held in the HUSM, it was possible to calculate a global reduction of dose of 55%. So, it can be said that, with the use of additional filters, the dose of radiation in the patient and medical team can be reduced without damage of the diagnosis. This reduction is still more significant for the professionals that work in more than one service of Hemodynamic.